'They are not my people': Barack Obama on lobbying and lobbyists. Issue 3 (25th June 2013) - McGrath, Conor
Abstract : This article traces the development of Barack Obama's sometimes ambiguous and sometimes antithetical attitudes and relationship to lobbyists. During his childhood in Indonesia, his stepfther was a lobbyist for a US oil company. Obama engaged himself in what many would consider to be lobbying in his career as a 'community activist' in Chicago. As an Illinois state senator, he befriended lobbyists and enjoyed poker and basketball games with them, in addition to raising about two thirds of his campaign finance from big business, unions, and political action committees. In the US Senate, Obama involved in ethics reforms that curbed the influence of lobbyists. His presidential campaign rhetoric was hard‐hitting, often decrying the irresponsibility of lobbyists while he had a number of lobbyists in key positions in his campaign team. On his first full day in office, President Obama signed an executive order restricting lobbyists from working in his administration. He later banned registered lobbyists from having personal meeting with officials about economic stimulus projects. Both these pledges have, however, had unforeseen or unwelcome consequences. More recently, Obama decided to ban lobbyists from membership of federal advisory panels but continues to meet frequently with favored lobbyists and corporate executives behind closed doors. The article questions whether Obama's history in this area adds up to a coherent or principled track record or whether it simply relates a series of inconsistent and political decisions. Copyright © 2013 John Wiley & Sons, Ltd.